Lifting strength in two-person teamwork. Issue 2 (2nd April 2016) - Lee, Tzu-Hsien
Abstract : This study examined the effects of lifting range, hand-to-toe distance, and lifting direction on single-person lifting strengths and two-person teamwork lifting strengths. Six healthy males and seven healthy females participated in this study. Two-person teamwork lifting strengths were examined in both strength-matched and strength-unmatched groups. Our results showed that lifting strength significantly decreased with increasing lifting range or hand-to-toe distance. However, lifting strengths were not affected by lifting direction. Teamwork lifting strength did not conform to the law of additivity for both strength-matched and strength-unmatched groups. In general, teamwork lifting strength was dictated by the weaker of the two members, implying that weaker members might be exposed to a higher potential danger in teamwork exertions. To avoid such overexertion in teamwork, members with significantly different strength ability should not be assigned to the same team.